The changes of serum zinc, copper, and selenium levels in epileptic patients: a systematic review and meta-analysis. Issue 9 (1st September 2020) - Jia, Wanying; Song, Yang; Yang, lei; Kong, Jingjing; Boczek, Tomasz; He, Zhenwei; Wang, Yuting; Zhang, Xiaohong; Hu, Huiyuan; Shao, Dongxue; Tang, Hong; Xia, Liguang; et al.
ABSTRACT: Introduction: It is widely accepted that trace elements have been implicated in various metabolic processes. Valproic acid (VPA) is a remarkably safe and effective antiepileptic drug. There is no consensus option regarding the fluctuations in serum zinc (Zn), copper (Cu), and selenium (Se) in epileptic patients treated with VPA. We applied a meta-analysis to systematically assess the effects of VPA on serum ions in these patients. Areas covered: In this study, we performed a meta-analysis of the changes in serum Zn, Cu, and Se levels in human samples of healthy controls, epileptic patients, and patients treated with VPA. Twenty-two published analyzable studies were selected by searching the databases of PubMed, China National Knowledge Infrastructure (CNKI), Google Scholar, Web of Science, EMBASE, WAN FANG and Vip. Expert opinion: Serum Se levels in epileptic patients were decreased compared to healthy controls. Serum Zn levels in patients with VPA treatment were significantly lower than those in epileptic patients. The results of this meta-analysis are instructive for the intake of trace elements such as Zn, Cu, and Se in the diet balance of patients with epilepsy treated with VPA. Meanwhile, this study provides a theoretical basis for the combined use of other drugs that affect the intake and absorption of trace elements and VPA.